Cyclic Yield Reversal in Steel Building Connections (T.R. Higgins Award) - Popov, Egor P.; Pinkney, R. Bruce (Engineering Journal, 1971)
For the most part, plastic analysis and design have in the past been directed toward the study of proportional, monotonically increasing loading to failure. This type of loading is not entirely realistic for many applications, however. The concepts of a shakedown analysis, while enlarging the scope of plastic analysis, result in a structure which ultimately responds elastically, after a few cycles of inelastic action. Severe earthquakes, on the other hand, may induce considerable repeated inelastic action in a structure, especially at the joints. This has motivated study of steel members and connections subjected to repeated and reversed loading. Except for an earlier paper by Bertero and Popov, no tests of this type appear to have been conducted in the United States, although intensive research into the problem has been carried out in Japan. Described herein are tests of 24 connection specimens subjected to various cyclic, quasi-static loading sequences. In addition to the behavior and the manner of failure of the beams and their connections to the columns, the hysteretic response of the beams under repeated and reversed loadings received particular attention.